SPECIAL ECONOMIC ZONES – A DRIVER OF REGIONAL DEVELOPMENT AND INDUSTRIAL MODERNIZATION (Global Conference on Multidisciplinary Research and Innovation, 2026)
In the current era of globalization, one of the most important tasks for governments is to reduce regional economic disparities, modernize industry, and ensure sustainable economic growth. In particular, as competition for capital, technology, and skilled labor intensifies, it becomes crucial to implement effective mechanisms that accelerate regional development. Special economic zones (SEZs) have emerged as such mechanisms and are widely applied in international practice.